2013
DOI: 10.1002/eji.201242858
|View full text |Cite
|
Sign up to set email alerts
|

Loss of methylation at the IFNG promoter and CNS‐1 is associated with the development of functional IFN‐γ memory in human CD4+T lymphocytes

Abstract: Cytokine memory for IFN-γ production by effector/memory Th1 cells plays a key role in both protective and pathological immune responses. To understand the epigenetic mechanism determining the ontogeny of effector/memory Th1 cells characterized by stable effector functions, we identified a T-cell-specific methylation pattern at the IFNG promoter and CNS-1 in ex vivo effector/memory Th1 cells, and investigated methylation dynamics of these regions during the development of effector/memory Th1 cells. During Th1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
6
42
0
1
Order By: Relevance
“…As shown in Fig. 1B, two ROI in the IFNG gene locus were selected, the promoter and CNS-1 (located 4.2 kb upstream of the transcriptional start site) (19). The analysis of DNA methylation status of the two ROI by bisulfite pyrosequencing showed that whereas Th17/Th1, nonclassic Th1, and classic Th1 cells had a marked demethylation, Th17 cells and naive CD4 + Th cells were characterized by a complete methylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Fig. 1B, two ROI in the IFNG gene locus were selected, the promoter and CNS-1 (located 4.2 kb upstream of the transcriptional start site) (19). The analysis of DNA methylation status of the two ROI by bisulfite pyrosequencing showed that whereas Th17/Th1, nonclassic Th1, and classic Th1 cells had a marked demethylation, Th17 cells and naive CD4 + Th cells were characterized by a complete methylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation of the ROI was assessed by pyrosequencing of bisulfite-specific PCR products using standard procedures (Varionostic, Ulm, Germany), as described previously by Dong et al (19). Briefly, 40 ng bisulfite-converted DNA was PCR amplified for the ROI of the IL17A, IL17F, IFNG, RORC2, and TBX21 genes using bisulfite-DNA-specific primers (Table I) in a PCR using the following program: 95˚C for 3 min; 50 cycles of 95˚C for 35 s, annealing temperature (Table I) for 35 s, and 72˚C for 40 s; and a final extension at 72˚C for 10 min.…”
Section: Dna Methylation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…40 Although the underlying mechanism is not completely understood, it was shown that IL-12 activates STAT4 that could further limit recruitment of DNA methyltransferase 41 leading to DNA demethylation. In addition, NK cells preactivated with IL-12/15/18 showed increased STAT5 phosphorylation in response to low doses of IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the original classification of circulating memory CD4 T cells into Th1 and Th2 cells,82 functional compartmentalization of antigen‐experienced T cells has become a favorite exercise of immunologists 83, 84, 85. We have shown that GATA3 mediates the epigenetic imprinting of the interleukin‐4 ( Il4 ) gene,86, 87 and how imprinting of the interferon‐γ ( Ifng ) gene is induced by STAT4 88, 89. Most importantly, we and others have shown that imprinting of cytokine genes in activated naive T cells but not in memory T cells requires progression through the S phase of the first cell division.…”
Section: Circulating Memory T Lymphocytesmentioning
confidence: 99%